Self-Cohesion - Edan, Ayad Kareem; Al-Khayri, Arwa Muhammad Rabee’ (Al-Adab Journal, 2022)
Self is considered the cornerstone of an individual's personality where healthy self comes as a result of healthy development. A healthy self-esteemed person is capable of facing daily obstacles and has a systematic personality working for achieving real objectives. On the contrary, a non-healthy self-esteemed person is suffering from severe restlessness and disconnectedness resulting from bad experience with their parents. The present study aims at;Measuring the self-cohesion of state employeesIdentify differences according to (gender, age, marital status).For the purpose of achieving the objectives of the current research, the researcher built the Self-Cohesion Scale according to Heinz Kohut (1971), which consisted of 41 final paragraphs and its validity and reliability were verified and the scale was applied in its final form to the research sample of 400 employees for both types, which were chosen by the random stratified method. And after applying the research tool and using statistical methods, including the T-test for one sample, the T-test for two independent samples, and the Pearson correlation coefficient.The results that the study has come up with are as follows:The state employees have self-cohesion.There are no differences according to (gender, age, marital status) in self-cohesion.The researcher suggested a set of recommendations and suggestions